2015
DOI: 10.1590/s0004-28032015000300013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Polymorphisms in the Interleukin 18 Gene Promotor (-137 G/C and -607 C/A) in Patients Infected With Hepatitis C Virus From the Brazilian Amazon

Abstract: The present results suggest a possible role of the -607 IL-18 gene promoter polymorphism in the pathogenesis of hepatitis C virus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In consistence of the current findings, the result of Yang and Liu 30 and the result of Abdelraheem 31 indicated that there were no evidence for association between À607 C/A polymorphism and chronicity HCV infection. On the other hand, studies by An et al 17 and Santos et al 12 reported that patients carrying genotype A/C at position À607 were found to be at higher risk of persistent HCV infection. Further studies are needed to explore this point.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In consistence of the current findings, the result of Yang and Liu 30 and the result of Abdelraheem 31 indicated that there were no evidence for association between À607 C/A polymorphism and chronicity HCV infection. On the other hand, studies by An et al 17 and Santos et al 12 reported that patients carrying genotype A/C at position À607 were found to be at higher risk of persistent HCV infection. Further studies are needed to explore this point.…”
Section: Discussionmentioning
confidence: 96%
“…11 Several studies suggested a possible role of IL28 or Single Nucleotide Polymorphisms (SNPs) of the gene IL-18 at positions À607 in clearance of HCV infection. 11,12 There were no data, so far, concerning the role of IL18 polymorphism in HCV-genotype 4 patients regarding therapeutic outcome of sofosbuvir and daclatasvir therapy.…”
mentioning
confidence: 99%
“…IL18 -137G and IL18 -607C alleles have been involved in the development of different diseases. The allele IL18 -607C has been linked to hepatitis C susceptibility [30] and chronic obstructive pulmonary disease [31], and the genotype C/C has been associated with higher IL-18 production in multiple sclerosis [32]; IL18 -137G was associated with the risk of arthritis [10] and IL18 -137G/C genotype with oral cancer [12]. More specifically with regard to CP, Li et al [33] showed in a meta-analysis study, involving nine case-control studies and a total of 576 patients with periodontitis and 458 healthy controls, that the IL18 -607C and IL18 -137G alleles were associated with an increased risk of periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Associations of other polymorphisms of IL-18 gene have also been reported by previous studies [100,101]. Additionally, there are several investigations which proved the roles of IL-18 polymorphisms in the risk of HCV chronic infection and its related complications [102][103][104][105][106][107]. Like IL-18, IL-1β and its receptor gene polymorphisms also have significant correlations with viral hepatitis chronic forms, the virus's replication and virus related liver cirrhosis and HCC [108][109][110][111][112].…”
Section: Inflammasomes; the Crucial Inducers Of Chronic Inflammation mentioning
confidence: 53%